Foreign trade development between Ukraine and the EU in agricultural sphere: specifics and prospects - Nepriadkina, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article examines the current state and analyzes the specificity of the further development of foreign trade in agricultural sphere between Ukraine and the EU countries. The countries of the European Union are important trade partners of Ukraine. The largest share in foreign trade between the EU and Ukraine goes to agricultural products and the food industry. Therefore, at present, steps are taken to deepen cooperation between Ukraine and the European Union in the field of agro-industrial complex. Unlike exports, the import of domestic agricultural products largely depends on the volume of investment in the industry, both domestic and external. This may indicate that the investments are not significant, or they are not carried out in the export-oriented industries. The expected benefits of trade preferences are advantages such as simplified access to the European market for some Ukrainian industrial products as well as agricultural ones